PENGARUH MOTIVASI SUAMI DAN PARITAS TERHADAP KECEMASAN IBU HAMIL MENJELANG PERSALINAN - Asriaty Dinopawe; Bazrul Makatita; Kharisma L Alerbitu (Jurnal Pendidikan Kesehatan, 2021)
This study aims to determine the relationship between husband motivation and parity on anxiety of pregnant women before childbirth in Lakor sub district, Southwest Maluku district. This is an analytical observational study with a cross section approach. The population and sample in this study were 32 pregnant women in Yamluly Village, Lakor District, Southwest Maluku Regency, using total sampling technique. The data collection method used a questionnaire. The results showed that most of the respondents in Yamluly Village, Lakor District, Southwest Maluku Regency had the husband motivation in the less supportive category, amounting to 18 respondents or 56.2 percent, parity in the primiparous category amounted to 21 respondents or 65.6 percent and had anxiety. totaled 22 respondents or 68.8 percent. The results of the analysis using the Fishers Exact Test showed a P value of 0.001, P value less than 0.05. The conclusion is that there is a relationship between husband motivation and parity on the anxiety of pregnant women in facing childbirth in Yamluly village, Lakor sub district, Southwest Maluku district